Comparative Study of the Resveratrol Content of Twenty-one Italian Red Grape Varieties - Vincenzi, S.; Tomasi, D.; Gaiotti, F.; Lovat, L.; Giacosa, S.; Torchio, F.; Río Segade, S.; Rolle, L. (South African Journal of Enology and Viticulture, 2016)
The content of resveratrol and some related stilbenes (piceids and piceatannol) in 21 Italian red grape varieties growing in the same edapho-climatic conditions and at the same stage of ripening was measured. Some varieties, like Barbera, Schiava gentile, Corvina and Marzemino, showed a trans-resveratrol content in the skin two to three times higher than the average content of all varieties. Trans- and cis-piceids were found in concentration higher than that of resveratrol, confirming both to be important contributors to the pool of health-promoting molecules present in grapes. Considering the total amount of stilbenes, the highest content was found in Barbera, Franconia, Negroamaro, Corvina and Marzemino, whereas other varieties, such as Montepulciano, Dolcetto, Croatina, Refosco and Primitivo, seem to synthesise very low amounts of these compounds. Barbera grapes also contain a relatively high concentration of transpiceatannol, a stilbene with even higher antioxidant properties than resveratrol, which means that it could be an interesting variety as a source of health-promoting molecules.